The Effects of Photobiomodulation of 808 nm Diode Laser Therapy at Higher Fluence on the in Vitro Osteogenic Differentiation of Bone Marrow Stromal Cells - Amaroli, Andrea; Agas, Dimitrios; Laus, Fulvio; Cuteri, Vincenzo; Hanna, Reem; Sabbieti, Maria Giovanna; Benedicenti, Stefano (Frontiers in Physiology, 2018)
The literature has supported the concept of mesenchymal stromal cells (MSCs) in bone regeneration as one of the most important applications in oro-maxillofacial reconstructions. However, the fate of the transplanted cells and their effects on the clinical outcome is still uncertain. Photobiomodulation (PBM) plays an important role in the acceleration of tissue regeneration and potential repair. The aim of this in vitro study is to evaluate the effectiveness of PBM with 808nm diode laser therapy, using a flat-top hand-piece delivery system at a higher-fluence (64J/cm2) irradiation (1W, continuous-wave) on bone marrow stromal cells (BMSCs). The BMSCs of 3 old female Balb-c mice were analyzed. The cells were divided into two groups: irradiated group and control group. In the former the cells were irradiated every 24 hours during 0 day (T0), 5 (T1), 10 (T2) and 15 (T3) days, whereas the control group was non-irradiated. The results have shown that the 64J/cm2 laser irradiation has increased the Runt-related transcription factor 2 (Runx2). Runx2 is the most important early marker of osteoblast differentiation. The higher-fluence suppressed the synthesis of adipogenic transcription factor (PPARγ), the pivotal transcription factor in adipogenic differentiation. Also, the osteogenic markers such as Osterix (Osx) and alkaline phosphatase (ALP) were upregulated with an increase in the matrix mineralization. Furthermore, western blotting data demonstrated that the laser therapy has induced a statistically valid increase in the synthesis of transforming growth factor 1 (TGF-β1) but had no effects on the tumor necrosis factor (TNF) production. The data has statistically validated the down-regulation of the important pro-inflammatory cytokines such as interleukin IL-6, and IL-17 after 808nm PBM exposition. An increase in anti-inflammatory cytokines such as IL-1rα and IL-10 was observed. These in vitro studies provide for first time the initial proof that the PBM of the 808nm diode laser therapy with flat-top hand-piece delivery system at a higher-fluence irradiation of 64J/cm2 (1W/cm2) can modulate BMSCs differentiation in enhancing osteogenesis.